KEBIJAKAN KRIMINAL PENANGGULANGAN CYBER BULLYING TERHADAP ANAK SEBAGAI KORBAN - Wenggedes Frensh Frensh; Syafruddin Kalo; Mahmud Mulyadi; Chairul Bariah (USU LAW JOURNAL, 2017)
ABSTRACT The result of this study shows that the present indonesia criminal policy dealing with cyber bullying either the penal policy or the non penal policy, they both can be used to prevent the act of cyber bullying. From the penal side, indonesia government uses criminal code and Law No. 11/2011 Information and electronic transactions  to prevent the act of cyber bullying. From the non penal side, government has done the cultural approach, moral and education approach, scientific approach and technology prevention. The future criminal policy in handling all act of cyber bullying in indonesia needs improvement and change. From the future penal side, there should be connectivity in the main criminal law system between criminal code and other constitutions besaide criminal code. The concept of criminal code needs to be validated by considering the comparative aspects towards the constitutions among other countries dealing with cyber bullying. From the future non penal side, there should be more moral approach/education, technology prevention, global approach (international cooperation), government role, media role and media of journalism role.   Keywords : Criminal Policy, Prevention, Cyber Bullying, Children, Victim